Simple, fast, cost-efficient, reliable, and highly automated DNA content analysis of cells in adherent cultures - Čížková, Jana; Filipová, Alžběta; Carrillo, Anna; Ehrlichová, Marie; Spálenková, Alžběta; Magdolenová, Alžbeta; Hájek, Miroslav; Horák, Pavel; Erbenova, Aneta; Šinkorová, Zuzana (Cytometry. Part A, 2024)
The most commonly used flow cytometric (FCM) analysis of cellular DNA content relies on ethanol fixation followed by RNA digestion and propidium iodide (PI) intercalation into double-stranded DNA. This is a laborious and time-consuming procedure that is subject to systematic errors due to centrifugation and washing steps associated with sample preparation. It can adversely affect the reliability of the results. Here, we present a modified concept of DNA quantification in adherent cell lines by FCM that involves neither ethanol fixation nor any washing and cell transferring steps. Our high throughput assay of adherent cell lines reduces sample-processing time, requires minimal workload, provides a possibility for automation, and, if needed, also allows a significant reduction in the size of individual samples. Working with a well-proven commercial tool-The BD CycletestTM Plus DNA Reagent Kit-primarily designed for cell cycle analysis and aneuploidy determination in experimental and clinical samples, we suggest a novel, very efficient, and robust approach for DNA research in adherent cell cultures.
Keywords: reprodukovatelnost výsledků; Automation; DNA; aneuploidie; průtoková cytometrie; buněčná adheze; Humans; Cell Adhesion; lidé; Flow Cytometry; Reproducibility of Results; buněčný cyklus; Cell Cycle; automatizace; Aneuploidy